Nanoscale wetting controls reactive Pd ensembles in synthesis of dilute PdAu alloy catalysts - Kang Rui Garrick Lim; Cameron J. Owen; Selina K. Kaiser; Prahlad K. Routh; Montserrat Mendoza; Kyoo-Chul K. Park; Taek-Seung Kim; Sadhya Garg; Jules A. Gardener; Lorenzo Russotto; Christopher R. O’Connor; Marianne Bijl; et al. (Nature Communications)
Abstract The performance of bimetallic dilute alloy catalysts is largely determined by the size of minority metal ensembles on the nanoparticle surface. By analyzing the synthesis of catalysts comprising Pd8Au92 nanoparticles supported on silica using surface-sensitive techniques, we report that whether Pd overgrowth occurs before or after Au nanoparticle deposition onto the support controls the surface Pd ensemble size and abundance. These differences in Pd ensembles influence catalytic reactivity in H2–D2 isotope exchange and benzaldehyde hydrogenation, which, in correlation with theoretical calculations, is used to elucidate the active site(s) in each reaction. To clarify how the synthetic sequence controls the formation of Pd ensembles, we combine numerical wetting calculations and molecular dynamics simulations (with a machine-learned force field) to visualize Pd deposition and migration on the nanoparticle surface, respectively. Our results suggest that the nanoparticle–support interface restricts nanoparticle accessibility to Pd deposition, which consequently controls the Pd ensemble size, illustrating the critical role of nanoscale wetting phenomena during bimetallic catalyst preparation.